2023
DOI: 10.1021/acs.jnatprod.2c01124
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Activity of Cyclotides: Toxicity Against Caenorhabditis elegans

Abstract: Cyclotides are a unique family of stable and cyclic mini-proteins found in plants that have nematicidal and anthelmintic activities. They are distributed across the Rubiaceae, Violaceae, Fabaceae, Cucurbitaceae, and Solanaceae plant families, where they are posited to act as protective agents against pests. In this study, we tested the nematicidal properties of extracts from four major cyclotide-producing plants, Oldenlandia affinis, Clitoria ternatea, Viola odorata, and Hybanthus enneaspermus, against the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Cyclotides with a stable ring structure can easily penetrate pests' bodies and destroy them from the inside. 83,84,88 The interaction between cyclotides and pest cells is closely linked to the hydrophobic patch and bioactive site present on their structural surface. This connection plays a significant role in the disruption of cell membranes, leading to cell lysis.…”
Section: Membrane-acting Of Cyclotidementioning
confidence: 99%
See 2 more Smart Citations
“…Cyclotides with a stable ring structure can easily penetrate pests' bodies and destroy them from the inside. 83,84,88 The interaction between cyclotides and pest cells is closely linked to the hydrophobic patch and bioactive site present on their structural surface. This connection plays a significant role in the disruption of cell membranes, leading to cell lysis.…”
Section: Membrane-acting Of Cyclotidementioning
confidence: 99%
“…This connection plays a significant role in the disruption of cell membranes, leading to cell lysis. 72,83,88,[97][98][99] The CCK motif serves to effectively stabilize the structure of the cyclotide, thereby preventing any potential structural rearrangement that may occur upon interaction with receptors. 100 Some studies have also shown that cyclotides are highly toxic in the early stages of the insect's life cycle, the juvenile phase contributing to great devastation on the flora when they need a lot of nutrients to mature.…”
Section: Membrane-acting Of Cyclotidementioning
confidence: 99%
See 1 more Smart Citation
“…Brazil boasts one of the planet's richest biodiversities, making it a significant source of natural, plant-based products. A variety of plant species have yielded crude aqueous extracts (ACEs) that exhibit noteworthy nematicidal effectiveness against M. incognita egg hatchability and juvenile mortality [23][24][25] Notably, several species within the Fabaceae family, including those within the genus Arachis, have shown promise as potential sources of nematotoxic compounds [26,27].…”
Section: Introductionmentioning
confidence: 99%